ORIENTALIST STEREOTYPES REFLECTD IN “DUNE” BY FRANK HERBERT - Three Anggano Putra Bakti; Ni Luh Nyoman Seri Malini; Ni Ketut Sri Rahayuni (Peneliti.net, 2026)
This study examines Dune by Frank Herbert as a work of postcolonial criticism through Edward Said’s theory of Orientalism, focusing on how Western–Eastern power relations are constructed and justified within the narrative. Using a qualitative methodology based on close reading and textual analysis of the novel, the research identifies orientalist binary oppositions that position the East as inferior and the West as naturally authoritative. The findings reveal that the Fremen are consistently represented through four orientalist stereotypes which are barbaric, exotic, fanatic, and timeless, which frame them as physically powerful yet culturally and politically backward. In contrast, Paul Atreides embodies Western rationality and authority, enabling him to gain epistemic power by interpreting Fremen ideology, manipulating prophecy, and exploiting religious fervor to facilitate imperial domination; although Dune acknowledges Paul’s awareness of the devastation he causes, the novel ultimately reinforces orientalist structures by portraying colonial authority as necessary, inevitable, and civilizing.